Poplar plum blossom-shaped nickel-cobalt bimetallic selenide / oxide heterojunction composite electrode material and preparation method and application thereof

By using the bayberry-shaped nickel-cobalt bimetallic selenide/oxide heterojunction composite electrode material in magnesium-lithium hybrid battery, the heterojunction structure of nano-tipes and nanoparticles is used to solve the problem of low conductivity of transition metal oxides. Performance issues achieve efficient charge transfer and structural stability, and improve the overall performance of magnesium lithium batteries.

CN119315009APending Publication Date: 2025-01-14ZHONGYUAN ENGINEERING COLLEGE
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411438165.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The low conductivity of transition metal oxides leads to redox reactions mainly occur on their surfaces, reducing the utilization efficiency and electrochemical stability of active materials, and affecting the performance of magnesium-lithium hybrid batteries.

Method used

Using the nickel-cobalt bimetallic selenide/oxide heterojunction composite electrode material in bayberry, the nanoparticles are grown on the surface of the nanospikes to form hollow structures and heterojunctions, which improve the charge transfer efficiency and structural stability, and utilize selenides and The synergistic effects of oxides enhance electrochemical properties.

Benefits of technology

It significantly improves the charge transfer efficiency and rate performance of magnesium-lithium hybrid batteries, enhances specific capacity and structural stability, and improves the kinetics and cyclic stability of electrochemical reactions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119315009A_ABST
    Figure CN119315009A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of nano materials, and discloses a poplar-blossom-shaped nickel-cobalt bimetallic selenide / oxide heterojunction composite electrode material and a preparation method and application thereof. The preparation method comprises the following steps: dissolving cobalt salt, nickel salt and urea in deionized water and an ethanol solution, and carrying out hydrothermal reaction to obtain a nickel-cobalt bimetallic precursor; and mixing selenium powder with the precursor, and carrying out thermal decomposition and selenylation reaction to obtain the populus-shaped nickel-cobalt bimetallic selenide / oxide heterojunction composite electrode material. The composite electrode material is a multiphase heterojunction, and the structure improves the charge transfer efficiency, so that the electrochemical performance is improved. In addition, the interior of the nano thorn is hollow, the nano particles form a poplar plum blossom shape on the surface of the nano thorn, the morphology can shorten the ion transmission path, the number of active sites and the contact area between the material and electrolyte are increased, and therefore the electrochemical reaction rate is increased. When the material is used as a positive electrode material to be applied to a magnesium-lithium hybrid battery positive electrode, the rate capability and the cycling stability of the battery can be remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of nanomaterials, and in particular to a bayberry flower-shaped nickel-cobalt bimetallic selenide / oxide heterojunction composite electrode material and a preparation method and application thereof. Background Art

[0002] Mg-Li hybrid batteries have advantages such as high safety and fast ion dynamics, which make them a promising emerging energy storage system. At present, the research focus of Mg-Li hybrid batteries is to explore electrode materials with high theoretical capacity, stable structure, long cycle life and fast dynamic speed. Designing high-performance electrode materials has important scientific and practical significance. The optimization of structure and morphology is an effective way to expand the specific surface area of ​​electrode materials and improve the storage capacity of Mg / Li. Transition metal oxides have the advantages of low cost, good electrochemical activity, high natural abundance and high theoretical capacitance, and have broad application prospects in the field of energy storage. However, their low conductivity causes the redox reaction to occur mainly on their surface, thereby reducing the utilization efficiency of active materials. Constructing heterojunction structures is an effective way to activate the electrochemical reaction of electrodes. The heterojunction of materials is formed by lattice matching of two or more components with different properties through crystal plane coupling. The heterojunction interface can show the complementary advantages and synergistic effects of different components. Nanomaterials exist in various forms, such as zero-dimensional (0D) nanoparticles and quantum dots; one-dimensional nanowires, nanotubes and nanobelts; two-dimensional nanosheets and nanosheets; and 3D porous nanonetworks. From 0D to 3D nanostructures, each type of nanostructure has its advantages and limitations in energy storage applications. Nanoparticles exhibit pseudocapacitance as battery materials. Nanoparticles have the characteristics of small size, large specific surface area and many active sites. As electrode materials, they can make good contact with the electrolyte, thereby accelerating electrochemical reactions. However, nanoparticles can aggregate together, which is equivalent to a single resistor in series, resulting in higher resistance and poor conductivity of the material. In order to fully utilize the advantages of nanoparticles and make up for their shortcomings, active nanoparticles can be modified on the surface of conductive (1D) nanothorns to prevent their aggregation and re-accumulation, which is also conducive to the storage of charge.

[0003] The problem of poor conductivity of transition metal oxides can be solved from two aspects. First, by adding transition metal selenides to form a heterojunction composite material. Secondly, adjust the structure and morphology of the material to improve the utilization efficiency of the active material, thereby improving the electrochemical performance. For example, Adv. Mater. 2021, 33, 2007539 discloses that in oxide positive electrode materials, even if the inserted magnesium has another structure, it is easy to form rock salt clusters similar to magnesium oxide in the parent phase, resulting in poor cyclability. How to select and prepare suitable precursors, how to improve the conductivity of oxides, and then design the material structure, which is of research significance for improving material performance. Summary of the invention

[0004] In order to overcome the above problems, the purpose of the present invention is to provide a bayberry flower-shaped nickel-cobalt bimetallic selenide / oxide heterojunction composite electrode material and its preparation method and application, so as to solve the problem that the low conductivity of transition metal oxides causes the redox reaction to mainly occur on their surface, thereby reducing the utilization efficiency of active materials, electrochemical stability and rate performance.

[0005] To achieve the above object, the technical solution of the present invention is implemented as follows: A bayberry flower-shaped nickel-cobalt bimetallic selenide / oxide heterojunction composite electrode material comprises nanothorns and nanoparticles grown on the surface of the nanothorns; the interior of the nanothorns is a hollow structure, and the tails of the nanothorns are connected to form a hollow structure; the nanothorns and the nanoparticles are both composed of metal selenide / oxide and form a heterostructure.

[0006] The preparation method of the above-mentioned bayberry flower-shaped nickel-cobalt bimetallic selenide / oxide heterojunction composite electrode material comprises the following steps: (1) A certain amount of cobalt chloride hexahydrate, nickel chloride hexahydrate and urea were dissolved in a mixed solvent of deionized water and anhydrous ethanol to form a red mixed solution under magnetic stirring. A high-pressure reactor was used to perform a hydrothermal reaction in a forced air heating oven. The solution was naturally cooled to room temperature and washed alternately with deionized water and alcohol for three times. The pink precipitate was collected by centrifugation and dried to obtain a sea urchin-like precursor. The formation process of the sea urchin-like precursor is as follows: First, the dissociated metal ions react with OH - and CO3 2- Rapid reaction to obtain an irregular solid core. At the beginning of the reaction, due to the high concentration of metal ions (Co 2+ and Ni 2+ ), the solid core has almost no cracks. As the reaction proceeds, the concentration of metal ions gradually decreases, and the remaining ones are gradually captured by NH3 through their coordination, forming [M(NH3)4] 2+ (M = Ni or Co), which marks the end of solid core growth. At the same time, NH3 acts as a carrier, retaining the metal ions moving to the top of the short nanorods with high surface energy, resulting in the preferential growth of the product at the top of the short nanorods, causing the short nanorods to slowly transform into long nanorods. With the growth of nanorods and the consumption of metal ions, the molar ratio of NH3 to metal ions gradually expands to more than 4. At this time, [M(NH3)4] 2+ The complex slowly transforms into [M(NH3)6] 2+, with an octahedral structure and good stability. During this process, some metal ions, under the action of strong coordination forces, escape from the edges and internal defects of the solid core due to the accumulation of chaotic crystals with a faster generation rate, resulting in a loose internal structure of the product when the reaction time exceeds 9h. On the contrary, nanorods with an ordered crystal structure show higher stability and continue to grow, further consuming metal ions until the molar ratio of NH3 to metal ions reaches 6:1, indicating that the solution is in a stable state and the reaction is over.

[0007] (2) The sea urchin-like precursor obtained in step (1) and selenium powder are fully mixed in a crucible at a molar ratio of 1: (0.8-1.5) and wrapped with tin foil. The mixture is calcined at high temperature under argon protection. After naturally cooling to room temperature, it turns into a black powder to obtain a bayberry flower-shaped nickel-cobalt bimetallic selenide / oxide heterojunction composite electrode material.

[0008] Furthermore, the volume ratio of deionized water to anhydrous ethanol in the mixed solvent of the above step (1) is (1-1.25):(0.75-1).

[0009] Furthermore, in the above step (1), the molar ratio of nickel chloride hexahydrate, cobalt chloride hexahydrate and urea is 1:(0.5-2):(26-40).

[0010] Furthermore, the concentration of nickel chloride hexahydrate in the mixed solution of step (1) above is 0.03-0.06 mol / L.

[0011] Furthermore, in the above step (1), the temperature of the hydrothermal reaction is 100-120° C., and the time is 10-14 h.

[0012] Furthermore, the conditions for the high temperature calcination treatment in the above step (2) are: under argon protection, the temperature is increased to 400-500° C. at a heating rate of 5° C. / min, and calcined for 3-5 hours.

[0013] In the preparation process of the heterojunction composite electrode material of the present invention, the formation of the bayberry flower-shaped nickel-cobalt bimetallic selenide / oxide heterojunction composite electrode material is attributed to the precursor being mixed with selenium powder and then being selenized in a crucible, that is, being selenized in a liquid phase environment. In this process, the thermal decomposition of the precursor produces some voids, and the volume will become larger. In the liquid phase environment, Se first contacts the surface of the nanothorns, and a part enters these voids, and a selenization reaction occurs. When the surface of the nanothorns is completely selenized, the liquid Se cannot enter the interior of the nanothorns, and can only be selenized with the part of the oxide that expands in volume, so it cannot be completely selenized. The part of the oxide that expands in volume is not continuous, so it is not the accumulation of nanoparticles, but grows on the nanothorns, so a bayberry flower-shaped composite electrode material is formed. In addition, due to incomplete selenization, the nanothorns and nanoparticles in the bayberry flower-shaped composite electrode material of the present invention are composed of oxides and selenides to form a heterogeneous structure, which improves the charge transfer efficiency and the utilization efficiency of the active material. In addition, this structure can alleviate the problem of volume expansion during the reaction, ensuring enhanced specific capacity and good structural stability.

[0014] In addition, the molar ratio of the precursor to the selenium powder in step (2) is different, resulting in a large difference in the phase and morphology of the synthesized materials under the same conditions. Therefore, the amount of selenium powder plays a key role in the synthesis of bayberry flower-shaped nickel-cobalt bimetallic selenide / oxide heterojunction composite electrode materials. The study found that when the molar ratio of the precursor to the selenium powder was 1:1.5, there were elemental selenium, oxides and selenides; when the molar ratio of the precursor to the selenium powder was 1:1.2, the phases began to contain only oxides and selenides, and nanoparticles began to grow on the nanothorns, but there was still an uneven situation. With the reduction of selenium powder, when the molar ratio of the precursor to the selenium powder was about 1:1, the nanothorns were full of nanoparticles, and the morphology was relatively uniform. The mass of selenium powder continued to decrease, and the nanoparticles were larger, which was not conducive to the electrochemical reaction. Therefore, it is necessary to explore the mass of the selenium powder involved in the reaction for the synthesis of bayberry flower-shaped nickel-cobalt bimetallic selenide / oxide heterojunction composite electrode materials.

[0015] A magnesium-lithium hybrid battery comprises a positive electrode, a negative electrode, an electrolyte and a separator, wherein the positive electrode comprises the above-mentioned bayberry flower-shaped nickel-cobalt bimetallic selenide / oxide heterojunction composite electrode material.

[0016] Furthermore, the above-mentioned positive electrode also includes a conductive agent, a positive electrode adhesive and a positive electrode current collector; the mass ratio of the bayberry flower-shaped nickel-cobalt bimetallic selenide / oxide heterojunction composite electrode material, the conductive agent and the positive electrode adhesive is (8-AB): (1+A): (1+B), wherein 0≤A≤2, 0≤B≤1.

[0017] The beneficial effects produced by the present invention are: (1) The present invention prepares bayberry flower-shaped nickel-cobalt bimetallic selenide / oxide heterojunction composite electrode materials, and the selection of precursor morphology is crucial. The sea urchin-like microscopic morphology is composed of multiple (1D) nanothorns, has a large specific surface area and a stable structure, and this structure has the effect of preventing nanoparticles from agglomerating. Therefore, selecting the sea urchin-like morphology as the precursor morphology is an effective strategy for optimizing electrode materials. The bayberry flower-shaped heterojunction composite electrode material can be prepared by mixing the precursor with selenium powder and calcining at high temperature. Specifically, unlike the selenization treatment with selenium vapor, the precursor in this process is selenized at high temperature in the liquid phase, that is, the thermal decomposition of the precursor produces some voids, and the volume will increase. In the liquid phase environment, Se first contacts the surface of the nanothorns, and a part of it enters these voids to cause a selenization reaction. When the surface of the nanothorns is completely selenized, the liquid cannot enter the interior of the nanothorns, and can only be selenized with the part of the oxide that has expanded in volume, so it cannot be completely selenized, and then a nickel-cobalt bimetallic selenide / oxide heterojunction is formed. Moreover, the part of the oxide that expands in volume is not continuous, so it is not the accumulation of nanoparticles, but growth on the nanothorns. In the selenization process, only the mass of the added selenium powder needs to be controlled to synthesize the bayberry flower-shaped nickel-cobalt bimetallic selenide / oxide heterojunction composite electrode material. The bayberry flower-shaped bimetallic selenide / oxide heterojunction composite material can significantly improve the charge transfer efficiency and rate performance of magnesium-lithium hybrid batteries. Studies have shown that the initial capacities of NiO / CoO, gas-phase selenization materials, and liquid-phase selenization materials (plum flower-shaped nickel-cobalt bimetallic selenide / oxide heterojunction composite electrode materials) are 187.9, 280.6, and 516.9 mAh g, respectively. -1 , indicating that liquid phase selenization is better. NiO / CoO at 0.1, 0.2, 0.3, 0.5, 0.8 and 1.0 A g -1 The discharge specific capacities at current densities of 88.9, 55.0, 37.8, 25.2, 16.5, and 12.5 mAh g -1 ; Plum blossom-shaped Ni-Co bimetallic selenide / oxide heterojunction composite electrode materials at 0.5, 0.8, 1.0, 1.5 and 2.0 A g -1 The discharge specific capacities at current densities of 435.7, 359.4, 338.8, 297.3, and 271.7 mAh g -1 .

[0018] (2) The bayberry flower-shaped nickel-cobalt bimetallic selenide / oxide heterojunction composite electrode material prepared by the present invention has a pore size of 1.7 nm and 5 nm, and has a microporous and mesoporous structure. Among them, the micropores can act as active sites for effective ion storage and ion buffer reservoirs to reduce volume expansion, ensure enhanced specific capacity and good structural stability. At the same time, the presence of mesopores is also conducive to the penetration of electrolytes and the transport of ions. In addition, the material has a large specific surface area, which increases the contact area with the electrolyte, thereby accelerating the electrochemical reaction kinetics. When this material is used as a positive electrode material for the first time in the positive electrode of a magnesium-lithium hybrid battery, the micropores and mesoporous structures make Mg 2+ and Li + Ions can be inserted and removed. The magnesium-lithium hybrid battery prepared with it as the positive electrode has a high conductivity at 0.5 A g -1 The current density is 435.7 mAh g -1 High storage capacity at 2 A g -1 269.9mAh g -1 Excellent rate performance. -1 After 500 cycles, the capacity retention rate was 74.9% and the Coulombic efficiency remained above 99.2%. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0020] Figure 1 Schematic diagram of the synthesis mechanism of the sea urchin-like precursor and bayberry flower-shaped nickel-cobalt bimetallic selenide / oxide heterojunction composite electrode material of the present invention.

[0021] Figure 2 The sea urchin-like precursor (a) in Example 1, the X-ray diffraction patterns of the precursor after thermal decomposition (b) and selenization (c), and the N2 adsorption-desorption isotherm and pore volume distribution diagram (d) of the bayberry flower-shaped nickel-cobalt bimetallic selenide / oxide heterojunction composite electrode material.

[0022] Figure 3 These are the EDS spectrum test results of the bayberry flower-shaped nickel-cobalt bimetallic selenide / oxide heterojunction composite electrode material prepared in Example 1; wherein (a) is the nanothorn of NCSO; (b) is the nanoparticle of NCSO; and (c) is the whole NCSO.

[0023] Figure 4The XPS analysis spectrum of the bayberry flower-shaped nickel-cobalt bimetallic selenide / oxide heterojunction composite electrode material prepared in Example 1; wherein (a) is a high-resolution spectrum of Co 2p; (b) is a high-resolution spectrum of Ni2p; (c) is a high-resolution spectrum of O 1s; and (d) is a high-resolution spectrum of Se3d.

[0024] Figure 5 The high-resolution transmission electron microscope images of the bayberry flower-shaped nickel-cobalt bimetallic selenide / oxide heterojunction composite electrode material of Example 1 and the Fourier transform images of each area (ad); (e) is a spatial position simulation image of a part of the crystal plane of NiSe2; (f) is a spatial position simulation image of a part of the crystal plane of CoO; (g) is a supercell model of NiSe2 and CoO; and (h) is a selected area electron diffraction image.

[0025] Figure 6 These are transmission electron microscope images of the bayberry flower-shaped nickel-cobalt bimetallic selenide / oxide heterojunction composite electrode material prepared in Example 1; wherein (a) is a transmission electron microscope image of the entire material; (bc) are transmission electron microscope images of the local nanothorns; and (d) is a high-resolution transmission electron microscope image.

[0026] Figure 7 This is the X-ray diffraction pattern of the bayberry flower-shaped nickel-cobalt bimetallic selenide / oxide heterojunction composite electrode material prepared in Example 1-5.

[0027] Figure 8 The scanning electron microscope images of the bayberry flower-shaped nickel-cobalt bimetallic selenide / oxide heterojunction composite electrode materials prepared in Examples 1-5; wherein, (a) is a scanning electron microscope image of a molar ratio of the precursor to the selenium powder of 1:1.5 (Example 2); (b) is a scanning electron microscope image of a molar ratio of the precursor to the selenium powder of 1:1.2 (Example 3); (c) is a scanning electron microscope image of a molar ratio of the precursor to the selenium powder of 1:1 (Example 1); (d) is a scanning electron microscope image of a molar ratio of the precursor to the selenium powder of 1:0.9 (Example 4); and (e) is a scanning electron microscope image of a molar ratio of the precursor to the selenium powder of 1:0.8 (Example 5).

[0028] Fig. 9 Schematic diagram of the energy storage mechanism and structure-activity relationship of the bayberry flower-shaped nickel-cobalt bimetallic selenide / oxide heterojunction composite electrode material prepared by the present invention.

[0029] Fig.10The performance CV curves and pseudocapacitance analysis of the bayberry flower-shaped nickel-cobalt bimetallic selenide / oxide heterojunction composite electrode material prepared in Example 1 when applied to a battery; wherein, (a) is a CV curve applied to a pure lithium battery; (b) is a CV curve applied to a pure magnesium battery; (c) is a CV curve applied to a magnesium-lithium hybrid battery; (d) is a CV curve at different scanning speeds when applied to a magnesium-lithium hybrid battery; (e) is a Log i- log v curve, wherein A Slope, B Slope, C Slope, DSlope, ESlope and F Slope are respectively the slopes of the redox peaks of AD at different positions in Figure (d) at different scanning speeds; (f) is the capacitance contribution (shaded area) in the CV curves at different scanning speeds.

[0030] Fig.11 The electrochemical performance of the bayberry flower-shaped nickel-cobalt bimetallic selenide / oxide heterojunction composite electrode material prepared in Example 1 for magnesium-lithium hybrid batteries; (a) is a long cycle performance diagram; (b) is a rate performance diagram; (c) is a NCSO at a current density of 1 A g -1 (d) is the constant current charge-discharge cycle curve of NCSO at different current densities; (e) is a comparison chart of different battery specific capacities and power densities.

[0031] Fig.12 The following are scanning electron microscope images of the composite materials prepared in Comparative Examples 1 and 2; wherein (a) is Comparative Example 1; and (b) is Comparative Example 2.

[0032] Fig.13 The graphs are a comparison of the electrochemical performance of the composite electrode materials prepared in Comparative Example 1, Comparative Example 2 and Example 1 for magnesium-lithium hybrid batteries; wherein (a) is a comparison of the rate performance between Comparative Example 1 and Example 1; and (b) is a comparison of the capacities of the first 10 cycles between Comparative Examples 1-2 and Example 1.

[0033] Fig.14 When the bayberry flower-shaped nickel-cobalt bimetallic selenide / oxide heterojunction composite electrode materials with different proportions of selenium powder are used in magnesium-lithium hybrid batteries, the -1 Electrochemical performance of 100 cycles after activation for 30 cycles at a current density of . DETAILED DESCRIPTION

[0034] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] Example 1 The preparation method of the bayberry flower-shaped nickel-cobalt bimetallic selenide / oxide heterojunction composite electrode material of this embodiment comprises the following steps: (1) 237.9 mg of cobalt chloride hexahydrate (1 mmol), 118.8 mg of nickel chloride hexahydrate (0.5 mmol), and 1 g of urea were dissolved in a mixed solution of 10 ml of deionized water and 6 ml of anhydrous ethanol to form a red solution under magnetic stirring. The solution was heated in a high-pressure reactor at 120°C in a forced air heating oven for 12 h, cooled naturally to room temperature, washed alternately with deionized water and alcohol for 3 times, and the pink precipitate was collected by centrifugation and dried to obtain a sea urchin-like nickel-cobalt precursor. (2) 108 mg of the precursor (1 mmol) of step (1) and 81 mg of selenium powder (1 mmol) were fully mixed in a crucible and wrapped with tin foil. Under argon protection, the mixture was heated to 400 °C at a heating rate of 5 °C / min and maintained for 4 hours. After cooling naturally to room temperature, it turned into a black powder to obtain a nickel-cobalt bimetallic selenide / oxide bayberry flower-shaped electrode material, which was labeled as NCSO.

[0036] Figure 1 Schematic diagram of the synthesis mechanism of the sea urchin-like precursor and the nickel-cobalt bimetallic selenide / oxide bayberry flower-shaped electrode material in Example 1. Specifically, the precursor (Ni 1 / 3 Co 2 / 3 (CO3) 1 / 2 (OH)·0.11H2O). OH required for the reaction - and CO2- 3 are produced by the hydrolysis of urea, and the sources of nickel and cobalt are NiCl2 and CoCl2, respectively. The melting point of selenium powder is 217℃, and selenium powder is liquid at 400℃. The thermal decomposition of the precursor generates NiO / CoO, CO2 and H2O, and also produces a large number of vacancies. At the same time, some vacancies are occupied by liquid selenium. NiSe2 / CoSe2 is generated by NiO / CoO and liquid Se. Therefore, NiO / CoO is the skeleton of the nanothorns on the sea urchin, and NiSe2 / CoSe2 exists near these vacancies (nanothorn surface and nanoparticles). The nanothorns are mainly composed of NiO / CoO, while the nanoparticles are mainly composed of NiSe2 / CoSe2. Since the precursor is selenized in a liquid environment, the nanoparticles cannot be completely selenized, so a part of NiO / CoO is retained in the nanoparticles. Therefore, NiO / CoO@NiSe2 / CoSe2 (NCSO) with a bayberry flower-like structure was finally synthesized.

[0037] Figure 2 a is the X-ray diffraction pattern of the sea urchin-like precursor in Example 1, which illustrates the successful synthesis of the precursor phase. Figure 2b and 2c are the X-ray diffraction diagrams of the thermal decomposition and selenization of the precursor, respectively. It can be seen from the figure that the thermal decomposition product of the precursor is NiO / CoO, and the selenization product is NCSO. The synthesis mechanism is shown in the following formula: Figure 2 The XRD diffraction peaks of NiO / CoO in c are lower while those of NiSe2 / CoSe2 are higher; Figure 2 d is the N2 adsorption-desorption isotherm and pore volume distribution diagram (inset) of the bayberry flower-shaped nickel-cobalt bimetallic selenide / oxide heterojunction composite electrode material prepared in Example 1. It can be seen that the pore diameters of the material are 1.7 nm and 5.0 nm, indicating that the material has microporous and mesoporous structures. In addition, the specific surface area is 16.7941 m 2 g -1 , which can increase the contact area between the material and the electrolyte and accelerate the electrochemical reaction.

[0038] Figure 3 a is the EDS spectrum test of NCSO nanothorns, Figure 3 b is the EDS spectrum test of NCSO nanoparticles. Figure 3 c is the EDS spectrum test of NCSO; it can be seen from the figure that the oxygen content on the nanothorns is relatively high, and the selenium content on the nanoparticles is relatively high. Overall, the atomic number O:Se=1:1. The nanothorns are mainly composed of NiO / CoO, while the nanoparticles are mainly composed of NiSe2 / CoSe2.

[0039] Figure 4 This is the XPS analysis spectrum of NCSO prepared in Example 1. It can be seen from the figure that the elements present in the material are Co, Ni, O and Se, which are consistent with the EDS test results. High-resolution Co 2p XPS spectrum ( Figure 4 a) can also be divided into two pairs of peaks, corresponding to Co 2p 3 / 2 and Co 2p 1 / 2 The peaks at 781.2 and 797.6 eV correspond to Co 3+ 2p 3 / 2 and 2p 1 / 2 , the peaks at 786.3 and 803.2 eV are satellite peaks. Meanwhile, the two peaks at 778.5 and 793.5 eV correspond to Co 2+ 2p 3 / 2 and 2p 1 / 2 . This indicates that Co in the composite material 2+ and Co 3+ Coexistence. High-resolution Ni 2p XPS spectra such as Figure 4 As shown in b, it can be divided into two pairs of peaks, corresponding to Ni 2p 3 / 2and Ni 2p 1 / 2 The peaks at 853.3 and 870.6 eV are Ni 2+ , the peaks at 856.1 and 873.8 eV are Ni 3+ In addition, 861.5 and 879.1 eV are satellite peaks. The results show that Ni 2+ and Ni 3+ The XPS spectrum of O 1s is as follows Figure 4 As shown in (c), the two peaks at 531.1 and 531.9 eV belong to the lattice oxygen of CoO and NiO phases, respectively. Figure 4 The Se3d XPS spectrum shown in d can also be fitted based on the two characteristic peaks. The peaks at 54.9 eV and 55.8 eV can be attributed to Se 3d 5 / 2 and Se3d 3 / 2 , which is a typical feature of metal-selenium bonds. The peak at 59.6 eV is attributed to SeO x , indicating the presence of Se-O bonds. It is possible that a small portion of selenium reacts with oxygen to form selenium oxide. The XPS analysis results are consistent with the XRD analysis results, indicating that the prepared samples are composed of NiO / CoO and NiSe2 / CoSe2.

[0040] Figure 5 (ad) are high-resolution transmission electron micrographs of the bayberry flower-shaped nickel-cobalt bimetallic selenide / oxide heterojunction composite electrode material prepared in Example 1. From the figure, it can be seen that the heterojunction surface is composed of the (2 0 0) crystal plane of NiSe2, the (2 0 0) crystal plane of CoSe2 and the (11 1) crystal plane of CoO. Figure 5 e, f are the spatial position simulation diagrams of some crystal planes of NiSe2 and CoO, respectively; the (2 0 0) crystal plane of NiSe2 and the (2 0 0) crystal plane of CoSe2 are both perpendicular to the (0 0 1) crystal plane, and the (2 0 0) crystal plane of CoSe2 and the (1 1 1) crystal plane of CoO are both perpendicular to the (0 -1 1) crystal plane, proving that the (2 0 0) crystal plane of NiSe2, the (20 0) crystal plane of CoSe2 and the (11 1) crystal plane of CoO can form a heterojunction surface. Figure 5 g is the supercell model of NiSe2 and CoO. The lattice constants of the two after the supercell are very close (24 Å long and 6 Å wide), which further proves the feasibility of the heterojunction. Figure 5 h is the corresponding selected area electron diffraction pattern, which shows the crystal planes of each phase.

[0041] Figure 6a is a transmission electron microscope image of the bayberry flower-shaped nickel-cobalt bimetallic selenide / oxide heterojunction composite electrode material prepared in Example 1 at low magnification. It can be seen that the nanothorns are connected at the tail to form a hollow structure, and the nanothorns are loaded with nanoparticles. This structure prevents the aggregation and re-accumulation of nanoparticles, reduces resistance, and is also conducive to charge storage. Figure 6 It can be seen from bc that the synthesized nanothorns are hollow. This hollow structure shortens the ion transmission path, increases the contact area between the material and the electrolyte, and accelerates the electrochemical reaction. Figure 6 d is a high-resolution transmission electron microscope image, which shows that the crystallinity of selenide is good, which is consistent with Figure 2 The analysis results of c are consistent, and the XRD diffraction peak of NiO / CoO in the bayberry flower-shaped nickel-cobalt bimetallic selenide / oxide heterojunction composite electrode material is lower.

[0042] Example 2 The preparation method of the bayberry flower-shaped nickel-cobalt bimetallic selenide / oxide heterojunction composite electrode material of this embodiment comprises the following steps: (1) 237.9 mg of cobalt chloride hexahydrate (1 mmol), 118.8 mg of nickel chloride hexahydrate (0.5 mmol), and 1 g of urea were dissolved in a mixed solution of 10 ml of deionized water and 6 ml of anhydrous ethanol to form a red solution under magnetic stirring. The solution was heated in a high-pressure reactor at 120°C in a forced air heating oven for 12 h, cooled naturally to room temperature, washed alternately with deionized water and alcohol for 3 times, and the pink precipitate was collected by centrifugation and dried to obtain a sea urchin-like nickel-cobalt precursor. (2) 108 mg of the precursor (1 mmol) of step (1) and 116 mg of selenium powder (1.5 mmol) were fully mixed in a crucible and wrapped with tin foil. Under argon protection, the mixture was heated to 400 °C at a heating rate of 5 °C / min and maintained for 4 hours. After cooling naturally to room temperature, it turned into a black powder to obtain a nickel-cobalt bimetallic selenide / oxide bayberry flower-shaped electrode material.

[0043] Example 3 The preparation method of the bayberry flower-shaped nickel-cobalt bimetallic selenide / oxide heterojunction composite electrode material of this embodiment comprises the following steps: (1) 237.9 mg of cobalt chloride hexahydrate (1 mmol), 118.8 mg of nickel chloride hexahydrate (0.5 mmol), and 1 g of urea were dissolved in a mixed solution of 10 ml of deionized water and 6 ml of anhydrous ethanol to form a red solution under magnetic stirring. The solution was heated in a high-pressure reactor at 120°C in a forced air heating oven for 12 h, cooled naturally to room temperature, washed alternately with deionized water and alcohol for 3 times, and the pink precipitate was collected by centrifugation and dried to obtain a sea urchin-like nickel-cobalt precursor. (2) 108 mg of the precursor (1 mmol) of step (1) and 91 mg of selenium powder (1.2 mmol) were fully mixed in a crucible and wrapped with tin foil. Under argon protection, the mixture was heated to 400 °C at a heating rate of 5 °C / min and maintained for 4 hours. After cooling naturally to room temperature, the mixture turned into a black powder to obtain a nickel-cobalt bimetallic selenide / oxide bayberry flower-shaped electrode material.

[0044] Example 4 The preparation method of the bayberry flower-shaped nickel-cobalt bimetallic selenide / oxide heterojunction composite electrode material of this embodiment comprises the following steps: (1) 237.9 mg of cobalt chloride hexahydrate (1 mmol), 118.8 mg of nickel chloride hexahydrate (0.5 mmol), and 1 g of urea were dissolved in a mixed solution of 10 ml of deionized water and 6 ml of anhydrous ethanol to form a red solution under magnetic stirring. The solution was heated in a high-pressure reactor at 120°C in a forced air heating oven for 12 h, cooled naturally to room temperature, washed alternately with deionized water and alcohol for 3 times, and the pink precipitate was collected by centrifugation and dried to obtain a sea urchin-like nickel-cobalt precursor. (2) 108 mg of the precursor (1 mmol) of step (1) and 71 mg of selenium powder (0.9 mmol) were fully mixed in a crucible and wrapped with tin foil. Under argon protection, the mixture was heated to 400 °C at a heating rate of 5 °C / min and maintained for 4 hours. After cooling naturally to room temperature, it turned into a black powder to obtain a nickel-cobalt bimetallic selenide / oxide bayberry flower-shaped electrode material.

[0045] Example 5 The preparation method of the bayberry flower-shaped nickel-cobalt bimetallic selenide / oxide heterojunction composite electrode material of this embodiment comprises the following steps: (1) 237.9 mg of cobalt chloride hexahydrate (1 mmol), 118.8 mg of nickel chloride hexahydrate (0.5 mmol), and 1 g of urea were dissolved in a mixed solution of 10 ml of deionized water and 6 ml of anhydrous ethanol to form a red solution under magnetic stirring. The solution was heated in a high-pressure reactor at 120°C in a forced air heating oven for 12 h, cooled naturally to room temperature, washed alternately with deionized water and alcohol for 3 times, and the pink precipitate was collected by centrifugation and dried to obtain a sea urchin-like nickel-cobalt precursor. (2) 108 mg of the precursor (1 mmol) of step (1) and 61 mg of selenium powder (0.8 mmol) were fully mixed in a crucible and wrapped with tin foil. Under argon protection, the mixture was heated to 400 °C at a heating rate of 5 °C / min and maintained for 4 hours. After cooling naturally to room temperature, it turned into a black powder to obtain a nickel-cobalt bimetallic selenide / oxide bayberry flower-shaped electrode material.

[0046] Figure 7The X-ray diffraction patterns of bayberry-shaped nickel-cobalt bimetallic selenide / oxide heterojunction composite electrode materials prepared with different ratios of selenium powder in Examples 1-5. When the molar ratio of the precursor to the selenium powder is 1:2, the phases obtained are Se and metal selenide; when the molar ratio is 1:1.5, the phases obtained are Se, NiSe2 and CoSe2; when the molar ratio is 1:1.2, Se disappears and the phases obtained are NiSe2 and CoSe2; when the molar ratio is 1:(0.8-1), only the characteristic peaks of NiSe2 and CoSe2 are present. The analysis results are similar to Figure 6 d results are consistent, the XRD diffraction peak of NiO / CoO in the bayberry flower-shaped nickel-cobalt bimetallic selenide / oxide heterojunction composite electrode material is lower. Figure 5 b The (1 1 1) crystal plane of CoO and Figure 5 The (2 2 2) crystal plane of NiO in h can confirm the existence of NiO / CoO.

[0047] Figure 8 The following is a scanning electron microscope image of the bayberry flower-shaped nickel-cobalt bimetallic selenide / oxide heterojunction composite electrode material prepared with different proportions of selenium powder. Figure 8 As shown in a, from the scanning electron microscope images with different magnifications, it can be seen that the nickel-cobalt bimetallic selenide / oxide is composed of nanoparticles and broken nanorods. Figure 8 be is a scanning electron microscope image of a bayberry flower-shaped nickel-cobalt bimetallic selenide / oxide heterojunction composite electrode material with different proportions of selenium powder; from the image, it can be found that when the molar ratio of the precursor to the selenium powder is about 1:1.2, the phases begin to consist of only oxides and selenides, and nanoparticles begin to grow on the nanothorns, but there is still an uneven situation. With the reduction of selenium powder, when the molar ratio of the precursor to the selenium powder is about 1:1, the nanothorns are full of nanoparticles, and the morphology is relatively uniform. The mass of selenium powder continues to decrease, and the nanoparticles are larger, which is not conducive to electrochemical reactions. Figure 8 c morphology is uniform, so Example 1 is the preferred embodiment.

[0048] Fig. 9 The schematic diagram of the energy storage mechanism and structure-activity relationship of the bayberry flower-shaped nickel-cobalt bimetallic selenide / oxide heterojunction composite electrode material prepared by the present invention. It can be seen that it shows the structural details from the micrometer scale to the nanometer scale. The oxide is adjacent to the selenide, and the electrons are mainly at the interface between the oxide and the selenide. The interface has a heterojunction surface, which is conducive to electron transmission, and most of the electrons are transmitted through the selenide with higher conductivity, ensuring rapid electron transfer. The nanothorns are used as a framework to reduce the transmission distance of ions, and the void space between the nanostructures can store electrolyte and reduce polarization.

[0049] Example 6 The preparation method of the bayberry flower-shaped nickel-cobalt bimetallic selenide / oxide heterojunction composite electrode material of this embodiment comprises the following steps: (1) 119 mg of cobalt chloride hexahydrate (0.5 mmol), 118.8 mg of nickel chloride hexahydrate (0.5 mmol), and 1.2 g of urea were dissolved in a mixed solution of 8 ml of deionized water and 8 ml of anhydrous ethanol to form a red solution under magnetic stirring. The solution was heated in a high-pressure reactor at 110°C in a forced air heating oven for 12 h, cooled naturally to room temperature, washed alternately with deionized water and alcohol for 3 times, and the pink precipitate was collected by centrifugation and dried to obtain a sea urchin-like nickel-cobalt precursor. (2) 108 mg of the precursor (1 mmol) of step (1) and 81 mg of selenium powder (1 mmol) were fully mixed in a crucible and wrapped with tin foil. Under argon protection, the mixture was heated to 450°C at a heating rate of 5°C / min and maintained for 4 hours. After cooling naturally to room temperature, the mixture turned into a black powder, and a nickel-cobalt bimetallic selenide / oxide bayberry flower-shaped electrode material was obtained.

[0050] Example 7 The preparation method of the bayberry flower-shaped nickel-cobalt bimetallic selenide / oxide heterojunction composite electrode material of this embodiment comprises the following steps: (1) 119 mg of cobalt chloride hexahydrate (0.5 mmol), 237.7 mg of nickel chloride hexahydrate (1 mmol), and 2 g of urea were dissolved in a mixed solution of 10 ml of deionized water and 8 ml of anhydrous ethanol to form a red solution under magnetic stirring. The solution was heated in a high-pressure reactor at 120°C in a forced air heating oven for 10 h, cooled naturally to room temperature, washed alternately with deionized water and alcohol for 3 times, and the pink precipitate was collected by centrifugation and dried to obtain a sea urchin-like nickel-cobalt precursor. (2) 108 mg of the precursor (1 mmol) of step (1) and 81 mg of selenium powder (1 mmol) were fully mixed in a crucible and wrapped with tin foil. Under argon protection, the mixture was heated to 500°C at a heating rate of 5°C / min and maintained for 3 hours. After cooling naturally to room temperature, it turned into a black powder to obtain a nickel-cobalt bimetallic selenide / oxide bayberry flower-shaped electrode material.

[0051] Example 8 The preparation method of the bayberry flower-shaped nickel-cobalt bimetallic selenide / oxide heterojunction composite electrode material of this embodiment comprises the following steps: (1) 285.5 mg of cobalt chloride hexahydrate (1.2 mmol), 202 mg of nickel chloride hexahydrate (0.85 mmol), and 1.5 g of urea were dissolved in a mixed solution of 8 ml of deionized water and 6 ml of anhydrous ethanol to form a red solution under magnetic stirring. The solution was heated in a high-pressure reactor at 100 °C in a forced air heating oven for 14 h, cooled naturally to room temperature, washed alternately with deionized water and alcohol for 3 times, and the pink precipitate was collected by centrifugation and dried to obtain a sea urchin-like nickel-cobalt precursor. (2) 108 mg of the precursor (1 mmol) of step (1) and 61 mg of selenium powder (0.8 mmol) were fully mixed in a crucible and wrapped with tin foil. Under argon protection, the mixture was heated to 400 °C at a heating rate of 5 °C / min and maintained for 5 hours. After cooling naturally to room temperature, it turned into a black powder to obtain a nickel-cobalt bimetallic selenide / oxide bayberry flower-shaped electrode material.

[0052] Example 9 The preparation method of the bayberry flower-shaped nickel-cobalt bimetallic selenide / oxide heterojunction composite electrode material of this embodiment comprises the following steps: (1) 214.1 mg of cobalt chloride hexahydrate (0.9 mmol), 118.8 mg of nickel chloride hexahydrate (0.5 mmol), and 1 g of urea were dissolved in a mixed solution of 9 ml of deionized water and 6 ml of anhydrous ethanol to form a red solution under magnetic stirring. The solution was heated in a high-pressure reactor at 110°C in a forced air heating oven for 12 h, cooled naturally to room temperature, washed alternately with deionized water and alcohol for 3 times, and the pink precipitate was collected by centrifugation and dried to obtain a sea urchin-like nickel-cobalt precursor. (2) 108 mg of the precursor (1 mmol) of step (1) and 81 mg of selenium powder (1 mmol) were fully mixed in a crucible and wrapped with tin foil. Under argon protection, the mixture was heated to 450°C at a heating rate of 5°C / min and maintained for 4 hours. After cooling naturally to room temperature, the mixture turned into a black powder, and a nickel-cobalt bimetallic selenide / oxide bayberry flower-shaped electrode material was obtained.

[0053] Comparative Example 1 The preparation method of the nickel-cobalt bimetallic oxide composite electrode material of this comparative example comprises the following steps: (1) 237.9 mg of cobalt chloride hexahydrate (1 mmol), 118.8 mg of nickel chloride hexahydrate (0.5 mmol), and 1 g of urea were dissolved in a mixed solution of 10 ml of deionized water and 6 ml of anhydrous ethanol to form a red solution under magnetic stirring. The solution was heated in a high-pressure reactor at 120°C in a forced air heating oven for 12 h, cooled naturally to room temperature, washed alternately with deionized water and alcohol for 3 times, and the pink precipitate was collected by centrifugation and dried to obtain a sea urchin-like nickel-cobalt precursor. (2) 108 mg of the precursor in step (1) was heated to 400° C. at a heating rate of 5° C. / min under argon protection and maintained for 4 hours. After naturally cooling to room temperature, it turned into a black powder to obtain a nickel-cobalt bimetallic oxide composite electrode material.

[0054] Comparative Example 2 The preparation method of the nickel-cobalt bimetallic selenide / oxide composite electrode material of this comparative example comprises the following steps: (1) 237.9 mg of cobalt chloride hexahydrate (1 mmol), 118.8 mg of nickel chloride hexahydrate (0.5 mmol), and 1 g of urea were dissolved in a mixed solution of 10 ml of deionized water and 6 ml of anhydrous ethanol to form a red solution under magnetic stirring. The solution was heated in a high-pressure reactor at 120°C in a forced air heating oven for 12 h, cooled naturally to room temperature, washed alternately with deionized water and alcohol for 3 times, and the pink precipitate was collected by centrifugation and dried to obtain a sea urchin-like nickel-cobalt precursor. (2) 81 mg of selenium powder from step (1) was placed in the upstream of the crucible, and 108 mg of the precursor was placed in the downstream of the crucible, and heated to 400°C at a heating rate of 5°C / min under argon protection conditions and maintained for 4 hours. After naturally cooling to room temperature, it turned into a black powder to obtain a nickel-cobalt bimetallic selenide / oxide composite electrode material.

[0055] Application Examples The bayberry flower-shaped nickel-cobalt bimetallic selenide / oxide heterojunction composite electrode material prepared in Example 1 was applied to pure lithium batteries, pure magnesium batteries and magnesium-lithium hybrid batteries. The specific preparation process of each battery is as follows: (1) Preparation and assembly of pure lithium batteries a. Preparation of positive electrode: 30 mg of the bayberry flower-shaped NiO / CoO@NiSe2 / CoSe2 composite electrode material, acetylene black and polytetrafluoroethylene were weighed in a mortar at a mass ratio of 8:1:1. After grinding for 30 minutes, the organic solvent N-methylpyrrolidone was added, stirred evenly and coated on a copper foil with a thickness of 14 μm. Then, it was placed in a 70°C vacuum oven for 12 hours and cut into 8 mm diameter round copper sheets by a punching machine. The mass of the bayberry flower-shaped NiO / CoO@NiSe2 / CoSe2 composite electrode material loaded on each copper sheet was 0.5 mg.

[0056] b. Negative electrode preparation: Use 400-grit sandpaper to polish the magnesium sheet until both sides are smooth. Then, use 0.1 M dilute hydrochloric acid solution to clean the polished magnesium sheet; then use distilled water and anhydrous ethanol to rinse the magnesium sheet to obtain a magnesium negative electrode with a smooth surface. Use a punch to cut the magnesium sheet into a disc with a diameter of 13 mm.

[0057] c. Battery assembly: In a glove box, use a coin-type battery CR2032, laminate the positive electrode, separator, negative electrode, and filler together, drip the electrolyte, and finally use a sealing machine to seal the battery to obtain a pure lithium battery; glass fiber separator is used as the separator, and the electrolyte is Li + (0.8 M LiCl and 0.4 M AlCl3 in tetrahydrofuran).

[0058] (2) Preparation and assembly of pure magnesium batteries The operation steps are the same as those for pure lithium batteries, except that the electrolyte is changed to Mg 2+ (0.4 M phenylmagnesium chloride and 0.4 M AlCl3 in tetrahydrofuran).

[0059] (3) Preparation and assembly of magnesium-lithium hybrid batteries The operation steps are the same as those for pure lithium batteries, except that the electrolyte is changed to Mg 2+ / Li + (0.8 M LiCl + 0.4 M AlCl3 + 0.4 M phenylmagnesium chloride in tetrahydrofuran solution) double salt electrolyte.

[0060] The above batteries were subjected to cyclic voltammetry tests. The specific test process is as follows: the three batteries were activated for 30 cycles and then subjected to cyclic voltammetry tests. Among them, the pure magnesium battery was activated at 0.05 A g -1 The current density was 0.2 mV s -1 ; Pure lithium battery at 0.5 A g -1 The current density was activated and the scan rate during the test was 0.2 mV s -1 ; Magnesium-lithium hybrid battery at 0.5 A g -1 The activation current density was 0.2-1.0 mV s -1 .

[0061] Fig.10 ac are the cyclic voltammograms of the bayberry flower-shaped nickel-cobalt bimetallic selenide / oxide heterojunction composite electrode material prepared in Example 1 in pure lithium (NCSO / / 0.8 M LiCl and 0.4 M AlCl3 in tetrahydrofuran solution / / magnesium foil), pure magnesium (NCSO / / 0.4 M phenylmagnesium chloride and 0.4 M AlCl3 in tetrahydrofuran solution / / magnesium foil) and magnesium-lithium hybrid battery (NCSO / / 0.8 MLiCl+0.4 M AlCl3+ 0.4 M phenylmagnesium chloride in tetrahydrofuran solution), respectively. Fig.10a It can be seen that the cathode peaks of pure lithium batteries are at 1.54, 1.27, 1.19, 0.84 and 0.50 V, and the anode peaks are at 0.32, 0.71, 1.07, 1.35 and 1.65 V. + From Fig.10 b It can be seen that the cathode peaks of the pure magnesium battery are at 1.63, 0.85 and 0.5 V, and the anode peaks are at 0.77, 1.55 and 1.80 V. 2+ From Fig.10 c It can be seen that the cathode peaks of the magnesium-lithium hybrid battery are at 1.76, 1.51, 1.05, 0.85 and 0.50 V, and the anode peaks are at 0.34, 0.76, 1.11, 1.40 and 1.80 V. Therefore, Mg 2+ The action voltage in the cathode peak of the magnesium-lithium hybrid battery is 1.76 V, which is due to the Li + Promotes Mg 2+ The cathode peak voltage increased from 1.63 V to 1.76 V due to the rapid transport of Li + The potential difference between the cathode peaks of 1.27 V and 1.19 V is small. The voltage decreases slightly during the cycle, so the cathode peak of 1.05 V is Li + In addition, 0.50 V and 0.85 V are caused by Mg 2+ and Li + In the anodic peak of MLHB, Mg 2+ At 1.80 V, Li + The effect is at 0.34 V and 1.11 V. This is because the Li + The increase in the concentration of Mg leads to a slight increase in the anodic peak potential of Li+. In addition, 0.76 V and 1.40 V are caused by Mg 2+ and Li + Therefore, magnesium-lithium hybrid battery is Mg 2+ and Li + participated in the reaction together. Fig.10 d is the CV curve of the bayberry flower-shaped nickel-cobalt bimetallic selenide / oxide heterojunction composite electrode material as the positive electrode of the magnesium-lithium hybrid battery at different scanning speeds. Three pairs of redox peaks can be clearly seen. Fig.10 e is the Log i- log v curve, and the slope is greater than 0.5 and less than 1, so the electrochemical reaction behavior of the electrode material is controlled by diffusion and pseudocapacitance behavior. Fig.10 f is 0.2 mV s -1 At the scan rate, the capacitance ratio of the NCSO electrode is 27.45%. When the scan rate is increased from 0.2 mV s-1 Increase to 1.0 mV s -1 The pseudocapacitive contribution increases from 27.45% to 46.25% when . These results indicate that the excellent rate performance of NCSO comes from its pseudocapacitive properties, which facilitates the rapid transport of ions.

[0062] Fig.11 The electrochemical performance of the bayberry flower-shaped nickel-cobalt bimetallic selenide / oxide heterojunction composite electrode material prepared in Example 1 was tested as the positive electrode of a magnesium-lithium hybrid battery. Fig.11 a is the long cycle performance of the hybrid battery. It can be seen from the figure that at 1 A g -1 After 500 cycles, the capacity retention rate was 74.9% and the Coulombic efficiency remained above 99.2%. Fig.11 b is the rate performance of the positive electrode material of the magnesium-lithium hybrid battery. It can be seen from the figure that the hybrid battery has a high rate performance at 0.5, 0.8, 1.0, 1.5 and 2.0 A g -1 The discharge specific capacities at current densities of 435.7, 359.4, 338.8, 297.3 and 271.7 mAhg -1 . Fig.11 c is the current density of 1 A g -1 The constant current charge-discharge cycle curve at 1 200 ℃ shows that the charge-discharge time can reach 280 h, indicating that the electrode of Example 1 has good cycle stability and reversibility. Fig.11 d is the discharge / charge voltage distribution diagram of the electrode of Example 1 at different current densities. It can be seen that the charging platform voltage is 0.90 V and the discharging platform voltage is 1.27 V. As the current density increases, the discharging platform voltage decreases slightly and the charging platform voltage increases slightly, which shows that the electrode of Example 1 has excellent rate performance and the polarization does not change much with the increase of current density. Fig.11 It can be seen from e that the specific capacity and rate performance of the battery using the composite material prepared in Example 1 as the positive electrode are much higher than those of other positive electrode materials of the same type of battery, indicating that the material has good long cycle performance, high capacity retention rate and excellent rate performance.

[0063] Fig.12 It is the scanning electron microscope picture of comparative example 1 and comparative example 2. Fig.12 a It can be seen that at high temperature, the nanothorns are decomposed into nanoparticles (NiO / CoO) by heat. NiO / CoO is the main framework of NCSO nanothorns. Fig.12 a It can be seen that there are many large particles after vapor phase selenization, and the morphology is not as good as that of liquid phase selenization.

[0064] The composite materials prepared in Comparative Example 1 and Comparative Example 2 and the heterojunction composite materials prepared in Examples 2-5 were respectively assembled into magnesium-lithium hybrid batteries according to the preparation and assembly method of Example 1. The electrochemical performance of the batteries was tested, and the results are shown in FIG. Fig.13 and Fig.14 shown.

[0065] Fig.13 This is a comparison chart of the electrochemical performance of the composite electrode materials prepared in Comparative Example 1, Comparative Example 2 and Example 1 for magnesium-lithium hybrid batteries. Fig.13 a is the rate performance of the hybrid battery after 30 cycles of activation (the battery used in Comparative Example 1 is at 0.1 A g -1 The battery used in Example 1 was activated at a current density of 0.5 A g -1 ), wherein Comparative Example 1 was activated at current densities of 0.1, 0.2, 0.3, 0.5, 0.8 and 1.0 A g -1 The discharge specific capacities at current densities of 88.9, 55.0, 37.8, 25.2, 16.5, and 12.5 mAh g -1 ; Example 1 at 0.5, 0.8, 1.0, 1.5 and 2.0 A g -1 The discharge specific capacities at current densities of 435.7, 359.4, 338.8, 297.3, and 271.7 mAh g -1 . Fig.13 b is a comparison chart of the first 10 cycles of capacity between comparative example 1-2 and example 1. It can be seen that the corresponding initial capacities are 187.9 (current density is 0.1 A g -1 )、280.6(current density is 0.1A g -1 ) and 516.9 mAh g -1 (The current density is 0.5 A g -1 ), which shows that Example 1 has excellent rate performance and high initial capacity, which is attributed to the existence of the heterojunction, which improves the charge transfer efficiency. In addition, the electrochemical performance of high-temperature liquid phase selenization is better than that of gas phase selenization.

[0066] Fig.14 The electrochemical performance diagram of the bayberry flower-shaped nickel-cobalt bimetallic selenide / oxide heterojunction composite electrode material with different proportions of selenium powder applied to magnesium-lithium hybrid batteries. The specific test process is as follows: the positive electrode is at 0.5 A g -1 After activation for 30 cycles at a current density of 1 A g -1The discharge capacity of 108:116 (Example 2), 108:91 (Example 3), 108:81 (Example 1), 108:71 (Example 4) and 108:61 (Example 5) are 252.2, 295.8, 334.9, 301.4 and 267.6 mAh g, respectively. -1 , indicating that Example 1 has a high discharge specific capacity and good cycle stability.

[0067] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A bayberry flower-shaped nickel-cobalt bimetallic selenide / oxide heterojunction composite electrode material, characterized in that: It includes nanothorns and nanoparticles grown on the surface of the nanothorns; the interior of the nanothorns is a hollow structure, and the tails of the nanothorns are connected to form a hollow structure; the nanothorns and nanoparticles are both composed of metal selenide / oxide and form a heterogeneous structure.

2. The method for preparing the bayberry flower-shaped nickel-cobalt bimetallic selenide / oxide heterojunction composite electrode material according to claim 1, characterized in that: Here are the steps: (1) dissolving nickel chloride hexahydrate, cobalt chloride hexahydrate and urea in a mixed solvent of deionized water and anhydrous ethanol to obtain a mixed solution; performing a hydrothermal reaction, washing, centrifuging and drying to obtain a sea urchin-like precursor; (2) After the sea urchin-like precursor is mixed with selenium powder, a high-temperature calcination treatment is performed to obtain a bayberry flower-shaped nickel-cobalt bimetallic selenide / oxide heterojunction composite electrode material.

3. The preparation method according to claim 2, characterized in that: The volume ratio of deionized water to anhydrous ethanol in the mixed solvent of step (1) is (1-1.25):(0.75-1).

4. The preparation method according to claim 3, characterized in that: In the step (1), the molar ratio of nickel chloride hexahydrate, cobalt chloride hexahydrate and urea is 1:(0.5-2):(26-40).

5. The preparation method according to claim 4, characterized in that: The concentration of nickel chloride hexahydrate in the mixed solution of step (1) is 0.03-0.06 mol / L.

6. The preparation method according to claim 5, characterized in that: The temperature of the hydrothermal reaction in step (1) is 100-120° C. and the time is 10-14 h.

7. The preparation method according to claim 6, characterized in that: In the step (2), the molar ratio of the sea urchin-like precursor to the selenium powder is 1:(0.8-1.5).

8. The preparation method according to claim 7, characterized in that: The conditions for the high temperature calcination treatment in step (2) are: in an argon protected environment, the temperature is increased to 400-500° C. at a heating rate of 5° C. / min, and calcined for 3-5 hours.

9. A magnesium-lithium hybrid battery, comprising a positive electrode, a negative electrode, an electrolyte and a separator, characterized in that: The positive electrode comprises the bayberry flower-shaped nickel-cobalt bimetallic selenide / oxide heterojunction composite electrode material according to claim 1.

10. The magnesium-lithium hybrid battery according to claim 9, characterized in that: The positive electrode also includes a conductive agent, a positive electrode adhesive and a positive electrode current collector; the mass ratio of the bayberry flower-shaped nickel-cobalt bimetallic selenide / oxide heterojunction composite electrode material, the conductive agent and the positive electrode adhesive is (8-AB): (1+A): (1+B), wherein 0≤A≤2, 0≤B≤1.

Citation Information

Cited By

  • FeTiO3-BiFeO3 heterojunction as well as preparation method and application thereof

    CN120749162A